PENGARUH DUE PROFESIONAL CARE PADA GOOD CORPORATE GOVERNANCE DAN IMPLIKASINYA PADA KUALITAS AUDIT INTERNAL - Darmawan, Ida Bagus Angga Baskara; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2017)
The purpose of this study was to analyze the effect of due professional care on good corporate governance and its implications on the quality of internal audit PT. Adira Finance Bali Province. This research was conducted in all branches of PT. Adira Finance Bali Province eight branch offices located in Bali region in 2016. The data collection is done by distributing questionnaires and analysis techniques using path analysis. Based on the analysis, the variables due professional care positive influence on good corporate governance PT. Adira Finance Bali Province. due professional care positive effect on the quality of internal audit PT. Adira Finance Bali Province. Good corporate governance variables have positive influence on the quality of internal audit PT. Adira Finance Bali Province. Good corporate governance is able to mediate or reinforce a positive influence on the quality of due professional care internal audit PT. Adira Finance Bali Province.
Keywords: Due Professional Care, Good Corporate Governance, Internal Audit Quality